Multilayer composite conductive flat filament, fabric and production process
By using a multi-layer composite conductive flat wire design in the conductive fibers, and using matrix resin and nano-conductive materials to form a conductive layer, the problems of poor conductivity and high cost are solved, and high conductivity and mechanical properties are improved.
Patent Information
- Application Number
- CN202510262892.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-06
AI Technical Summary
The existing conductive fibers have poor conductivity, high cost and are susceptible to environmental influences.
The multi-layer composite conductive flat wire is designed, and the conductive layer is composed of matrix resin, nanoconductive carbon black, carbon nanotubes and graphene. It is prepared by melt extrusion and tensile splitting processes to form a composite structure of the conductive layer and the intermediate layer.
It effectively improves the conductivity and mechanical properties of the conductive flat wire, solves the problem of easy peeling of the conductive layer, simplifies the production process and reduces production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of conductive fibers, and in particular to a multi-layer composite conductive flat yarn, a fabric and a production process. Background Art
[0002] Conductive fiber refers to chemical fiber, metal fiber, carbon fiber, etc. spun by mixing conductive medium into polymer. It has excellent performance in eliminating and preventing static electricity, which is much higher than antistatic fiber, and its specific resistance value is persistent and basically unaffected by humidity. Currently, most conductive fibers on the market are made by metal coating or doping with conductive particles, which have problems such as high cost, poor conductive stability, and susceptibility to environmental influence. Summary of the invention
[0003] In order to improve the conductive performance of conductive fibers, the present application provides a multi-layer composite conductive flat yarn, a fabric and a production process.
[0004] In the first aspect, the present application provides a multi-layer composite conductive flat wire, which adopts the following technical solution: A multi-layer composite conductive flat wire comprises a conductive layer and an intermediate layer. The raw materials of the conductive layer comprise the following components in parts by weight: 70-90 parts of base resin, 1-5 parts of nano conductive carbon black, 1-5 parts of carbon nanotubes, and 5-10 parts of graphene.
[0005] By adopting the above technical solution, nano-conductive carbon black, carbon nanotubes, and graphene conductive components are distributed in the conductive layer and located on the surface of the conductive flat wire, which effectively improves the conductivity and mechanical properties of the flat wire, solves the problem of easy peeling of the conductive layer, and simplifies the production process and reduces production costs.
[0006] In a specific embodiment, the base resin includes PET or PBT.
[0007] In a specific embodiment, the method for preparing the multi-layer composite conductive flat wire comprises the following steps: Firstly, the matrix resin, nano-conductive carbon black, carbon nanotubes and graphene are stirred and mixed evenly, melt-extruded, cooled and pelletized to obtain a conductive masterbatch; Polyester is selected as the raw material for the middle layer, and polyester and conductive masterbatch are added into a multi-layer extruder for melt extrusion. The conductive masterbatch forms a conductive layer on the surface, and the polyester forms an intermediate layer to obtain a film. The film is biaxially stretched and then split to obtain a multi-layer composite conductive flat wire, and each flat wire is wound separately.
[0008] By adopting the above technical scheme, the matrix resin, nano-conductive carbon black, carbon nanotubes and graphene are first stirred and extruded into granules to obtain a conductive masterbatch; then the conductive masterbatch and polyester are compositely extruded, and finally the obtained film is stretched and split to obtain a multi-layer composite conductive flat wire.
[0009] In the second aspect, the present application provides a fabric, which adopts the following technical solution: A fabric is made from the multi-layer composite conductive flat yarn.
[0010] By adopting the above technical solution, the fabric made by using the multi-layer composite conductive flat yarn in the present application has good conductive performance.
[0011] In a third aspect, the present application provides a fabric production process, which adopts the following technical solution: A production process for a fabric comprises the following steps: Pretreatment: immersing the multilayer composite conductive flat wire in a pretreatment solution, slowly adding ferric chloride hexahydrate and 4-methylbenzenesulfonic acid, fully reacting, then taking out, washing, and drying to obtain a pretreated flat wire; the raw materials of the pretreatment solution include the following components in parts by weight: 20-30 parts of water, 60-70 parts of ethanol, 0.5-1 parts of deacetylated chitosan fiber film powder, 1-3 parts of pyrrole, 0.1-0.5 parts of dispersant, and 0.1-0.5 parts of stabilizer; Weaving: Weaving warp yarns and weft yarns into strip-shaped or grid-shaped base cloth on a loom to obtain fabrics, wherein the warp and weft yarns are both pre-treated flat yarns.
[0012] By adopting the above technical solution, the multi-layer composite conductive flat yarn is first immersed in a pretreatment liquid for pretreatment to further improve the conductive property of the flat yarn, and then woven to obtain a fabric with good conductive property.
[0013] In a specific embodiment, the method for preparing the chitosan fiber film powder comprises the following steps: First, glacial acetic acid and dimethyl sulfoxide are stirred and mixed evenly, and then Triton X-100 is added and stirred to obtain a mixed solution; chitosan and polyethylene oxide are added to the mixed solution, and the mixture is stirred and mixed evenly to obtain a spinning solution, and electrospinning is performed to obtain a nanofiber membrane, and the nanofiber membrane is crushed to obtain chitosan fiber membrane powder.
[0014] In a specific embodiment, the weight ratio of the glacial acetic acid, the dimethyl sulfoxide, the Triton X-100, the chitosan, and the polyethylene oxide is 90: (9-11): (0.2-0.4): (2.0-2.2): (0.8-1.0).
[0015] By adopting the above technical solution, the ratio of glacial acetic acid, dimethyl sulfoxide, Triton X-100, chitosan and polyethylene oxide is further limited, so that the nanofiber membrane can be better formed.
[0016] In a specific embodiment, the dispersant includes one or more of sodium hexametaphosphate, sodium pyrophosphate, sodium dodecyl sulfate, sodium hexametaphosphate, and polyvinyl alcohol.
[0017] In a specific embodiment, the stabilizer includes one or more of polyethylene glycol, polyacrylic acid, and polyacrylamide.
[0018] In summary, the present application includes at least one of the following beneficial technical effects: In the present application, nano-conductive carbon black, carbon nanotubes, and graphene conductive components are distributed in the conductive layer and located on the surface of the conductive flat wire, which effectively improves the conductivity and mechanical properties of the flat wire, solves the problem of easy peeling of the conductive layer, simplifies the production process, and reduces the production cost; In the present application, the matrix resin, nano-conductive carbon black, carbon nanotubes, and graphene are first stirred and extruded to obtain a conductive masterbatch; then the conductive masterbatch and polyester are composite extruded, and finally the obtained film is stretched and split to obtain a multi-layer composite conductive flat wire; In the process of the present application, the multi-layer composite conductive flat yarn is first immersed in a pretreatment liquid for pretreatment to further improve the conductive properties of the flat yarn, and then woven to obtain a fabric with better conductive properties. DETAILED DESCRIPTION
[0019] The present application is further described in detail below in conjunction with embodiments.
[0020] All raw materials in the examples can be obtained commercially. The dispersant includes but is not limited to a mixture of one or more of sodium hexametaphosphate, sodium pyrophosphate, sodium dodecyl sulfate, sodium hexametaphosphate, and polyvinyl alcohol, preferably sodium dodecyl sulfate in this application; the stabilizer includes a mixture of one or more of polyethylene glycol, polyacrylic acid, and polyacrylamide, preferably polyethylene glycol in this application; the matrix resin includes but is not limited to one of PET or PBT, preferably PET in this application.
[0021] Preparation Example 1 Preparation Example 1 provides a method for preparing deacetylated chitosan fiber film powder, comprising the following steps: First, glacial acetic acid and dimethyl sulfoxide are stirred and mixed evenly, and then Triton X-100 is added and stirred to obtain a mixed solution; chitosan and polyethylene oxide are added to the mixed solution, and the mixture is stirred and mixed evenly to obtain a spinning solution, and electrostatic spinning is performed at 20-25° C. to obtain a nanofiber membrane, and the nanofiber membrane is crushed to obtain chitosan fiber membrane crumbs; wherein the weight ratio of glacial acetic acid, dimethyl sulfoxide, Triton X-100, chitosan and polyethylene oxide is 90:9:0.2:2.0:0.8.
[0022] Preparation Example 2 Preparation Example 2 provides a method for preparing deacetylated chitosan fiber membrane powder, comprising the following steps: First, glacial acetic acid and dimethyl sulfoxide are stirred and mixed evenly, and then Triton X-100 is added and stirred to obtain a mixed solution; chitosan and polyethylene oxide are added to the mixed solution, and the mixture is stirred and mixed evenly to obtain a spinning solution, and electrostatic spinning is performed at 20-25°C to obtain a nanofiber membrane, and the nanofiber membrane is crushed to obtain chitosan fiber membrane crumbs; wherein the weight ratio of glacial acetic acid, dimethyl sulfoxide, Triton X-100, chitosan and polyethylene oxide is 90:10:0.3:2.1:0.9.
[0023] Preparation Example 3 Preparation Example 3 provides a method for preparing deacetylated chitosan fiber membrane powder, comprising the following steps: First, glacial acetic acid and dimethyl sulfoxide are stirred and mixed evenly, and then Triton X-100 is added and stirred to obtain a mixed solution; chitosan and polyethylene oxide are added to the mixed solution, and the mixture is stirred and mixed evenly to obtain a spinning solution, and electrostatic spinning is performed at 20-25°C to obtain a nanofiber membrane, and the nanofiber membrane is crushed to obtain chitosan fiber membrane crumbs; wherein the weight ratio of glacial acetic acid, dimethyl sulfoxide, Triton X-100, chitosan and polyethylene oxide is 90:11:0.4:2.2:1.0. Example
[0024] Embodiment 1 provides a method for preparing a multi-layer composite conductive flat wire, comprising the following steps: First, 70 kg of base resin, 1 kg of nano-conductive carbon black, 1 kg of carbon nanotubes, and 5 kg of graphene are stirred and mixed evenly, melt-extruded, cooled, and pelletized to obtain a conductive masterbatch; wherein the base resin is PET; Polyester is selected as the raw material for the middle layer, and polyester and conductive masterbatch are added into a multi-layer extruder for melt extrusion. The conductive masterbatch forms a conductive layer on the surface, and the polyester forms an intermediate layer to obtain a multi-layer film. The film can be a three-layer or five-layer structure. In this embodiment, it has three layers, two conductive layers and an intermediate layer located between the conductive layers. The film is biaxially stretched and then split to obtain a multi-layer composite conductive flat wire, and each flat wire is wound separately; the weight ratio of the conductive masterbatch to polyester is 35:65. Example
[0025] Embodiment 2 provides a method for preparing a multi-layer composite conductive flat wire, comprising the following steps: First, 80 kg of matrix resin, 3 kg of nano-conductive carbon black, 3 kg of carbon nanotubes, and 7.5 kg of graphene are stirred and mixed evenly, melt-extruded, cooled, and pelletized to obtain a conductive masterbatch; wherein the matrix resin is PET; Polyester is selected as the raw material for the middle layer, and polyester and conductive masterbatch are added into a multi-layer extruder for melt extrusion. The conductive masterbatch forms a conductive layer on the surface, and the polyester forms an intermediate layer to obtain a multi-layer film. The film can be a three-layer or five-layer structure. In this embodiment, it has three layers, two conductive layers and an intermediate layer located between the conductive layers. The film is biaxially stretched and then split to obtain a multi-layer composite conductive flat wire, and each flat wire is wound separately; the weight ratio of the conductive masterbatch to polyester is 35:65. Example
[0026] Embodiment 3 provides a method for preparing a multilayer composite conductive flat wire, comprising the following steps: First, 90 kg of base resin, 5 kg of nano-conductive carbon black, 5 kg of carbon nanotubes, and 10 kg of graphene are stirred and mixed evenly, melt-extruded, cooled, and pelletized to obtain a conductive masterbatch; wherein the base resin is PET; Polyester is selected as the raw material for the middle layer, and polyester and conductive masterbatch are added into a multi-layer extruder for melt extrusion. The conductive masterbatch forms a conductive layer on the surface, and the polyester forms an intermediate layer to obtain a multi-layer film. The film can be a three-layer or five-layer structure. In this embodiment, it has three layers, two conductive layers and an intermediate layer located between the conductive layers. The film is biaxially stretched and then split to obtain a multi-layer composite conductive flat wire, and each flat wire is wound separately; the weight ratio of the conductive masterbatch to polyester is 35:65.
[0027] Application Example 1 Application Example 1 provides a fabric production process, comprising the following steps: Pretreatment: add 0.5kg of the deacetylated chitosan fiber membrane powder in Preparation Example 1, 1kg of pyrrole, 0.1kg of dispersant, 0.1kg of stabilizer, and 20kg of water to 60kg of ethanol, stir and mix evenly to obtain a pretreatment solution; immerse the multilayer composite conductive flat wire in Example 1 in the pretreatment solution for 25min, slowly add ferric chloride hexahydrate and 4-methylbenzenesulfonic acid, react fully, then take out, wash, and dry to obtain a pretreated flat wire; wherein the molar ratio of ferric chloride hexahydrate to pyrrole is 2.25:1; the concentration of 4-methylbenzenesulfonic acid is 0.1mol / L; the dispersant is sodium dodecyl sulfate; and the stabilizer is polyethylene glycol; Weaving: The warp yarn and the weft yarn are woven into a strip-shaped base cloth on a loom to obtain the fabric, wherein the warp and weft yarns are both pre-treated flat yarns.
[0028] Application Example 2 Application Example 2 provides a fabric production process, comprising the following steps: Pretreatment: 0.75 kg of the chitosan fiber membrane powder in Preparation Example 1, 2 kg of pyrrole, 0.3 kg of dispersant, 0.3 kg of stabilizer, and 25 kg of water were added to 65 kg of ethanol, and the mixture was stirred to obtain a pretreatment solution; the multilayer composite conductive flat wire in Example 1 was immersed in the pretreatment solution for 25 min, and ferric chloride hexahydrate and 4-methylbenzenesulfonic acid were slowly added, and then fully reacted, and then taken out, washed, and dried to obtain a pretreated flat wire; wherein the molar ratio of ferric chloride hexahydrate to pyrrole was 2.25:1; the concentration of 4-methylbenzenesulfonic acid was 0.1 mol / L; the dispersant was sodium dodecyl sulfonate; and the stabilizer was polyethylene glycol; Weaving: The warp yarn and the weft yarn are woven into a strip-shaped base cloth on a loom to obtain the fabric, wherein the warp and weft yarns are both pre-treated flat yarns.
[0029] Application Example 3 Application Example 3 provides a fabric production process, comprising the following steps: Pretreatment: 1 kg of the chitosan fiber membrane powder in Preparation Example 1, 3 kg of pyrrole, 0.5 kg of dispersant, 0.5 kg of stabilizer, and 30 kg of water were added to 70 kg of ethanol, and the mixture was stirred to obtain a pretreatment solution; the multilayer composite conductive flat wire in Example 1 was immersed in the pretreatment solution for 25 min, and ferric chloride hexahydrate and 4-methylbenzenesulfonic acid were slowly added, and then fully reacted, and then taken out, washed, and dried to obtain a pretreated flat wire; wherein the molar ratio of ferric chloride hexahydrate to pyrrole was 2.25:1; the concentration of 4-methylbenzenesulfonic acid was 0.1 mol / L; the dispersant was sodium dodecyl sulfate; and the stabilizer was polyethylene glycol; Weaving: The warp yarn and the weft yarn are woven into a strip-shaped base cloth on a loom to obtain the fabric, wherein the warp and weft yarns are both pre-treated flat yarns.
[0030] Application Example 4 Application Example 4 provides a fabric production process, comprising the following steps: Pretreatment: 0.75 kg of the chitosan fiber film powder in Preparation Example 2, 2 kg of pyrrole, 0.3 kg of dispersant, 0.3 kg of stabilizer, and 25 kg of water were added to 65 kg of ethanol, and the mixture was stirred to obtain a pretreatment solution; the multilayer composite conductive flat wire in Example 1 was immersed in the pretreatment solution for 25 min, and ferric chloride hexahydrate and 4-methylbenzenesulfonic acid were slowly added, and then fully reacted and then taken out, washed, and dried to obtain a pretreated flat wire; wherein the molar ratio of ferric chloride hexahydrate to pyrrole was 2.25:1; the concentration of 4-methylbenzenesulfonic acid was 0.1 mol / L; the dispersant was sodium dodecyl sulfate; and the stabilizer was polyethylene glycol; Weaving: The warp yarn and the weft yarn are woven into a strip-shaped base cloth on a loom to obtain the fabric, wherein the warp and weft yarns are both pre-treated flat yarns.
[0031] Application Example 5 Application Example 5 provides a fabric production process, comprising the following steps: Pretreatment: 0.75 kg of the chitosan fiber film powder in Preparation Example 3, 2 kg of pyrrole, 0.3 kg of dispersant, 0.3 kg of stabilizer, and 25 kg of water were added to 65 kg of ethanol, stirred and mixed evenly to obtain a pretreatment solution; the multilayer composite conductive flat wire in Example 1 was immersed in the pretreatment solution for 25 minutes, and ferric chloride hexahydrate and 4-methylbenzenesulfonic acid were slowly added, fully reacted, then taken out, washed, and dried to obtain a pretreated flat wire; wherein the molar ratio of ferric chloride hexahydrate to pyrrole was 2.25:1; the concentration of 4-methylbenzenesulfonic acid was 0.1 mol / L; the dispersant was sodium dodecyl sulfate; and the stabilizer was polyethylene glycol; Weaving: The warp yarn and the weft yarn are woven into a strip-shaped base cloth on a loom to obtain the fabric, wherein the warp and weft yarns are both pre-treated flat yarns.
[0032] Application Example 6 Application Example 6 provides a fabric production process, comprising the following steps: Pretreatment: 0.75 kg of the chitosan fiber membrane powder in Preparation Example 2, 2 kg of pyrrole, 0.3 kg of dispersant, 0.3 kg of stabilizer, and 25 kg of water were added to 65 kg of ethanol, and the mixture was stirred to obtain a pretreatment solution; the multilayer composite conductive flat wire in Example 2 was immersed in the pretreatment solution for 25 min, and ferric chloride hexahydrate and 4-methylbenzenesulfonic acid were slowly added, and then fully reacted and then taken out, washed, and dried to obtain a pretreated flat wire; wherein the molar ratio of ferric chloride hexahydrate to pyrrole was 2.25:1; the concentration of 4-methylbenzenesulfonic acid was 0.1 mol / L; the dispersant was sodium dodecyl sulfate; and the stabilizer was polyethylene glycol; Weaving: The warp yarn and the weft yarn are woven into a strip-shaped base cloth on a loom to obtain the fabric, wherein the warp and weft yarns are both pre-treated flat yarns.
[0033] Application Example 7 Application Example 7 provides a fabric production process, comprising the following steps: Pretreatment: 0.75 kg of the deacetylated chitosan fiber membrane powder in Preparation Example 2, 2 kg of pyrrole, 0.3 kg of dispersant, 0.3 kg of stabilizer, and 25 kg of water were added to 65 kg of ethanol, stirred and mixed evenly to obtain a pretreatment solution; the multilayer composite conductive flat wire in Example 3 was immersed in the pretreatment solution for 25 minutes, and ferric chloride hexahydrate and 4-methylbenzenesulfonic acid were slowly added, fully reacted, then taken out, washed, and dried to obtain a pretreated flat wire; wherein the molar ratio of ferric chloride hexahydrate to pyrrole was 2.25:1; the concentration of 4-methylbenzenesulfonic acid was 0.1 mol / L; the dispersant was sodium dodecyl sulfate; and the stabilizer was polyethylene glycol; Weaving: The warp yarn and the weft yarn are woven into a strip-shaped base cloth on a loom to obtain the fabric, wherein the warp and weft yarns are both pre-treated flat yarns.
[0034] Comparative application example 1 Comparative Application Example 1 provides a fabric production process, comprising the following steps: Pretreatment: 1kg of nano-conductive carbon black, 1kg of carbon nanotubes, 1.5kg of graphene, 0.1kg of dispersant, 0.1kg of stabilizer, and 80kg of water were stirred and mixed to obtain a pretreatment solution; the polyester fiber was immersed in the pretreatment solution for 30 minutes, and the conductive particles were evenly distributed on the surface of the polyester fiber by ultrasonic vibration, and then taken out and dried to obtain the pretreated fiber; wherein the dispersant was sodium dodecyl sulfate; and the stabilizer was polyethylene glycol; Weaving: The warp yarn and the weft yarn are woven into a strip-shaped base cloth on a loom to obtain the fabric, wherein the warp and weft yarns are both pretreated fibers.
[0035] Conductive performance: After washing the fabrics in each application example and comparative application example 100 times and drying them, the conductivity of the fabrics was measured. The higher the conductivity, the better the conductive performance of the fabric.
[0036] Table 1 Fabric performance test results
[0037] Combining Application Example 1 and Comparative Application Example 1, the conductive performance of the fabric in Application Example 1 is better. It can be seen that the fabric is made of the multi-layer composite conductive flat wire in the present application, and the nano-conductive carbon black, carbon nanotubes, and graphene conductive components in the flat wire are distributed in the conductive layer and located on the surface of the conductive flat wire, which effectively improves the conductivity of the flat wire, so that the fabric still has good conductive performance after being washed many times.
[0038] In combination with Application Examples 1-3, the conductive property of the fabric in Application Example 2 is the best. It can be seen that when preparing the pretreatment liquid, the raw material ratio in Application Example 2 is the best, thus achieving the best treatment effect on the flat yarn.
[0039] Combining Application Example 2, Application Example 4 and Application Example 5, the conductive performance of the fabric in Application Example 4 is the best. It can be seen that when preparing deacetylated chitosan fiber membrane crumbs, the ratio of glacial acetic acid, dimethyl sulfoxide, Triton X-100, deacetylated chitosan and polyethylene oxide in Preparation Example 2 is optimal, so that the deacetylated chitosan fiber membrane crumbs have the best performance.
[0040] Combining Application Example 4, Application Example 6 and Application Example 7, the conductive performance of the fabric in Application Example 6 is the best. It can be seen that when preparing the multi-layer composite conductive flat wire, the usage of the raw material matrix resin, nano-conductive carbon black, carbon nanotubes, and graphene is increased during melt granulation, and the conductive performance of the multi-layer composite conductive flat wire shows a trend of first increasing and then decreasing.
[0041] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A multi-layer composite conductive flat wire, comprising a conductive layer and an intermediate layer, characterized in that: The raw materials of the conductive layer include the following components in parts by weight: 70-90 parts of base resin, 1-5 parts of nano-conductive carbon black, 1-5 parts of carbon nanotubes, and 5-10 parts of graphene.
2. The multi-layer composite conductive flat wire according to claim 1, characterized in that: The base resin includes PET or PBT.
3. The multi-layer composite conductive flat wire according to claim 1, characterized in that: The preparation method of the multi-layer composite conductive flat wire comprises the following steps: Firstly, the matrix resin, nano-conductive carbon black, carbon nanotubes and graphene are stirred and mixed evenly, melt-extruded, cooled and pelletized to obtain conductive masterbatch; Polyester is selected as the raw material for the middle layer, and polyester and conductive masterbatch are added into a multi-layer extruder for melt extrusion. The conductive masterbatch forms a conductive layer on the surface, and the polyester forms an intermediate layer to obtain a film. The film is biaxially stretched and then split to obtain a multi-layer composite conductive flat wire, and each flat wire is wound separately.
4. A fabric, characterized in that: The fabric is made of the multi-layer composite conductive flat yarn as described in any one of claims 1 to 3.
5. A process for producing the fabric according to claim 4, characterized in that: The following steps are involved: Pretreatment: immersing the multilayer composite conductive flat wire in a pretreatment solution, slowly adding ferric chloride hexahydrate and 4-methylbenzenesulfonic acid, fully reacting, then taking out, washing, and drying to obtain a pretreated flat wire; the raw materials of the pretreatment solution include the following components in parts by weight: 20-30 parts of water, 60-70 parts of ethanol, 0.5-1 parts of deacetylated chitosan fiber film powder, 1-3 parts of pyrrole, 0.1-0.5 parts of dispersant, and 0.1-0.5 parts of stabilizer; Weaving: Weaving warp yarns and weft yarns into strip-shaped or grid-shaped base cloth on a loom to obtain fabrics, wherein the warp and weft yarns are both pre-treated flat yarns.
6. The production process of a fabric according to claim 5, characterized in that: The method for preparing the chitosan fiber film powder comprises the following steps: First, glacial acetic acid and dimethyl sulfoxide are stirred and mixed evenly, and then Triton X-100 is added and stirred to obtain a mixed solution; chitosan and polyethylene oxide are added to the mixed solution, and the mixture is stirred and mixed evenly to obtain a spinning solution, and electrospinning is performed to obtain a nanofiber membrane, and the nanofiber membrane is crushed to obtain chitosan fiber membrane powder.
7. The production process of a fabric according to claim 6, characterized in that: The weight ratio of the glacial acetic acid, the dimethyl sulfoxide, the Triton X-100, the chitosan, and the polyethylene oxide is 90:(9-11):(0.2-0.4):(2.0-2.2):(0.8-1.0).
8. The process for producing a fabric according to claim 5, characterized in that: The dispersant includes one or more of sodium hexametaphosphate, sodium pyrophosphate, sodium dodecyl sulfate, sodium hexametaphosphate, and polyvinyl alcohol.
9. The process for producing a fabric according to claim 5, characterized in that: The stabilizer includes one or more of polyethylene glycol, polyacrylic acid, and polyacrylamide.
Citation Information
Patent Citations
Graphene conductive polyester fibers and preparation method thereof
CN104164707A
High-strength conductive PP / MLLDPE plastics for flat yarns and preparation method for high-strength conductive PP / MLLDPE plastics
CN108586926A
Conductive container bag and preparation method thereof
CN119411280A
Base fabric for flexible container bag and flexible container bag using the base fabric
JP3322869B1
Cited By
Preparation method of flexible pressure-sensitive fiber fabric and flexible pressure-sensitive fiber fabric sensor
CN120211008A